Design of Accounting Learning Model Through the Positive Divergent Stimulation Under Mental Accounting Dilemma - Maharani, Satia Nur; Rahmawati, Setya Ayu (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
Scientific character affects the mental processes of a person who studies the science. The implication is that the ability to think differently to master accounting is strongly influenced by cognitive mental processes, namely mental accounting [10]. Meanwhile, the learning model that stimulates the divergent thinking process is one of the treffinger techniques. This model is known as Creative Problem Solving (CPS) which encourages a divergent process through a set of tools to solve problems, develop new ideas and manage change creatively [3]. To achieve the success of divergent thinking in accounting involves a cognitive construction process, namely mental accounting [10]. Meanwhile, mental accounting can be placed on positive cognitive processes, but also has negative roots and can develop perfectly as long as the learning process stimulates negative cognitive potential [7]. Therefore, this study investigates how accounting students achieve positive divergent thinking in cognitive mental accounting dilemmas through literature review. The study resulted in a positive divergent thinking model under mental accounting dilemmas.